Recent therapeutic advances in gynecologic oncology: evolving roles of immunotherapy, antibody–drug conjugates, and clinical trial innovations - Koshkimbayeva, Gaukhar; Amirkhanova, Akerke; Orazymbetova, Aiken; Nurakhova, Alma; Maimakova, Akmaral; Duisenbayeva, Altyn; Akhmad, Nurgulim; Abilova, Altyn; Abilbayeva, Arailym; Akhelova, Sholpan; Akhmentayeva, Dana; Seitaliyeva, Aida; et al. (Frontiers in Oncology, 2026)
Background and objectivesGynecologic cancers, including cervical, endometrial, and ovarian malignancies, remain among the leading causes of cancer-related illness and death in women worldwide. Despite progress in surgery and chemotherapy, resistance to conventional cytotoxic drugs continues to limit durable outcomes. The introduction of immune checkpoint inhibitors (ICIs) and antibody–drug conjugates (ADCs) has created new therapeutic opportunities by improving survival and overcoming resistance mechanisms. This review summarizes the latest clinical evidence on immunotherapy and ADC-based regimens, emphasizing their integration into current treatment strategies and the expanding roles of genomic profiling and artificial intelligence (AI) in personalized therapy.Materials and methodsRecent findings from major clinical trials such as RUBY, NRG-GY018, DUO-O, SORAYA, and DESTINY-PanTumor02 were evaluated along with updated FDA and NCCN recommendations. The analysis focuses on treatments that have demonstrated clinical benefit in advanced or recurrent disease, including pembrolizumab, dostarlimab, tisotumab vedotin, and mirvetuximab soravtansine. Combination strategies incorporating PARP inhibitors, antiangiogenic agents, and immune checkpoint blockade were also reviewed.ResultsCheckpoint inhibitors have achieved meaningful clinical benefits in patients with advanced or recurrent endometrial and cervical cancers, particularly in those with mismatch repair deficiency or PD-L1 expression. ADCs directed against tissue factor (TF) and folate receptor alpha have shown effectiveness in platinum-resistant cervical and ovarian cancers. Combination regimens that include ICIs, PARP inhibitors, or antiangiogenic therapy are yielding encouraging results in both first-line and maintenance settings. Advances in molecular profiling and biomarker-based patient selection, supported by AI applications, are further improving treatment precision in gynecologic oncology.ConclusionsImmunotherapy and ADCs represent major advances in the treatment of gynecologic cancers. Their growing integration into clinical practice has reshaped therapeutic approaches, while ongoing research continues to refine optimal combinations, address resistance, and enhance biomarker-guided selection. Future developments are expected to unite immunologic, genomic, and computational strategies to achieve personalized and durable outcomes for patients with gynecologic malignancies.